PENGARUH INSENTIF DAN LOYALITAS TERHADAP KINERJA DRIVER GOJEK DI KOTA PEKANBARU - RUDI SYAF PUTRA; DION OKTAMADE; INTAN PUTRI AZHARI (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to analyze the effect of incentives and loyalty on the performance of Gojek drivers in Pekanbaru City. The independent variables used are incentives and loyalty. While the dependent variable used is performance. This study uses a quantitative approach with multiple linear regression analysis models and the company population of all Gojek drivers in Pekanbaru City. The number of samples used in this study were 380 respondents. The results show that incentives have a positive effect on performance and loyalty has a positive effect on performance. Then incentives and loyalty simultaneously affect the performance of Gojek drivers in Pekanbaru City.